Dengue and Chikungunya virus circulation in Cameroon and Gabon: molecular evidence among symptomatic individuals. Issue 4 (29th April 2022) - Djeunang Dongho, Ghyslaine Bruna; Venturi, Giulietta; Fortuna, Claudia; Paganotti, Giacomo Maria; Severini, Carlo; L'Episcopia, Mariangela; Tsapi, Armand Tiotsia; Benedetti, Eleonora; Marsili, Giulia; Amendola, Antonello; Rezza, Giovanni; Sobze, Martin Sanou; et al.
Abstract : We report the molecular evidence of dengue virus (DENV) and chikungunya virus (CHIKV) infection in symptomatic individuals in Cameroon and Gabon, respectively. Arthropod-borne viruses (arboviruses) are distributed in the tropical or subtropical regions, with DENV having the highest burden. The morbidity and mortality related to arboviral diseases raise the concern of timely and efficient surveillance and care. Our aim was to assess the circulation of arboviruses [DENV, CHIKV, Zika virus (ZIKV)] among febrile patients in Dschang (West Cameroon) and Kyé-ossi (South Cameroon, border with Gabon and Equatorial Guinea). Dried blood spots were collected from 601 consenting febrile patients, and 194 Plasmodium spp.-negative samples were tested for the molecular detection of cases of DENV, CHIKV and ZIKV infection. Overall, no case of ZIKV infection was found, whereas one case of DENV infection and one case of CHIKV infection were detected in Dschang and Kyé-ossi, respectively, with the CHIKV-infected patient being resident in Gabon. Our findings suggest the need to establish an active surveillance of arbovirus transmission in Cameroon and bordering countries.